Biometrics of fruits, seeds and seedlings of Cenostigma tocantinum Ducke (Research, Society and Development, 2022)
Tree species have the potential to be used in different sectors and production chains. In this context, biometrics constitutes an important tool to identify the main characteristics intrinsic to the fruit and the seed. Therefore, the objective of this study was to biometrically characterize the fruits, seeds and seedlings of the species Cenostigma tocantinum Ducke, in order to obtain information on the variation of characteristics. For the evaluation of biometrics, 100 fresh fruits from different mother trees were used. The characteristics evaluated were: length, width and thickness of fruit and seeds, fruit weight, number of seeds per fruit, seedling emergence, shoot length, taproot and total seedlings. Variability was observed for the biometric characters related to the dimensions and weights of Cenostigma tocantinum fruits. The percentage of seedling emergence was 98%. The results found in this study can help in the differentiation and identification of the species, providing biometric data of important botanical characteristics and of the species in the initial stage of growth.